The Effect of Hyperhomocysteinemia on Motor Symptoms, Cognitive Status, and Vascular Risk in Patients with Parkinson’s Disease - Bilge Kocer; Hayat Guven; Isik Conkbayir; Selim Selcuk Comoglu; Sennur Delibas (Parkinson's Disease)
Factors related with hyperhomocysteinemia (HHcy) and the impact of HHcy in Parkinson’s disease (PD) are not well understood. We investigated the factors associated with increased levels of homocysteine (Hcy) and the relationship between HHcy and motor symptoms, cognitive status, and vascular risk in patients with Parkinson’s disease. Among 60 patients (29 males, 48.3%) with PD, the stage of the disease, the severity of clinical symptoms, and the patients’ cognitive status were measured using a modified Hoehn and Yahr Staging Scale (mHY), Unified Parkinson’s Disease Rating Scale (UPDRS) II and III, and Mini-Mental State Examination (MMSE), respectively. Patients were also noted for having dyskinesia and hallucinations. Serum vitamin B12, folic acid, and plasma Hcy ​​levels were measured. Furthermore, the presence of vascular risk factors was recorded. Finally, we investigated carotid artery intima-media thickening and stenosis using colour Doppler ultrasonography as well as the presence of ischemic lesions using brain imaging techniques. Plasma Hcy ​​levels were higher with advanced age and in males. In addition, there was an inverse relationship between Hcy ​​and vitamin B12 levels. There was no correlation between HHcy and the stage of the disease, severity of motor symptoms, cognitive status as assessed by the MMSE, vascular risk factors, carotid artery atherosclerotic findings, and ischemic brain lesions. Plasma Hcy levels may rise due to several factors in PD. However, the resulting HHcy has no significant effect on the clinical picture in terms of motor features, cognitive status, and vascular diseases.